The Moderating Role of Brand Awareness in The Relationship Between Brand Association and Intention to Pay Zakat in Indonesia Amil Zakat Institution - Muhammad, Doddy; Juhary, Ali; Cicih, Ratnasih (2019)
This research evaluated the impact of brand awareness, brand association, and interaction between brand awareness and brand association on the intention to pay zakat at Dompet Dhuafa Indonesia. Many brand studies on the intention to buy in profitoriented organizations have been conducted. So, this research was performed to see the impact of brand awareness and brand association in non-profit organizations such as amil zakat institution. The study used a quantitative research design using a 100 zakat payer sample to evaluate hypotheses empirically. The results show that brand association has a favorable impact intention to pay zakat. However, brand awareness does not become a moderating variable in the brand association's connection with the intention to pay zakat. The empirical research supplied academics with fruitful consequences by making an essential contribution to the literature on brand and zakat management.